Indigenous Engagement in Health Research in Circumpolar Countries: An Analysis of Existing Ethical Guidelines - Lavoie, Josée; Stoor, Jon Petter; Cueva, Katie; Healey Akearok, Gwen; Rink, Elizabeth; Viskum Lytken Larsen, Christina; Gladun, Elena (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
In this paper, we review existing ethical guidelines that support Circumpolar Indigenous Peoples’ engagement in health research. For this study, we collated national and regional ethical guidelines addressing health research engaging with Indigenous communities. Our study found that ethical guidelines addressing Indigenous engagement in health research have emerged in Canada and the U.S.A. Currently, there are no Indigenous-specific provisions in national guidelines, or legislation concerning health research engaging Indigenous peoples, in Denmark, Finland, Greenland, Norway, Sweden, or Russia. Where guidelines exist, they show considerable variations. We conclude that guidelines are essential to ensure that research undertaken in Indigenous communities is relevant and beneficial to those communities, is conducted respectfully, and that results are appropriately contextualized and accurate. We believe that our analysis might serve as a checklist to support the development of comprehensive guidelines developed by, or at least in partnership with, Arctic Indigenous communities.